In-situ iron oxide particle size and shape evolution during the dissolution in oxalic acid - Lausch, M.; Brockmann, P.; Schmitt, F.; Etzold, Bastian; Hussong, J. (Chemical Engineering Science, 2024)
In this study, the influence of temperature (40, 60 and 80 ∘C) and light exposure on the dissolution of [Formula presented] particles in aqueous, oxalic acid (0.45 mol/l) is experimentally investigated. A novel experimental setup, consisting of a vessel with undistorted optical access, allows the recording of dissolving particles using a video system. During post-processing, particles are automatically identified and their size and morphology are determined. Binning particles into discrete time-steps during the reaction yields heavy-tailed distributions characterized by a single parameter estimated through a maximum-likelihood estimation of a doubly truncated power-law fit. For the first time, up to three consecutive phases could be identified during the dissolution process of iron oxide particles. The contribution of each phase to the overall dissolution process is determined by a complex interplay between particle fragmentation, different reaction mechanisms and solid product formation. The initial phase is characterized by the fragmentation of larger particles with a more complex morphology, resulting in greater surface area available for reaction. In the second phase, fragmentation is less apparent and the available particle surface area is reduced. The transition to the third phase relies primarily on the supply of short wavelength light, which leads to the formation of a solid product that can increase the tracked particle diameter.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Iron oxide; Metal fuel; Oxalic acid; Particle morphology; Polydisperse suspension; Reductive dissolution